Investigating The Readiness and Satisfaction of Students and Lecturers For The Integration of Chatgpt in English Academic Writing at Ganesha University of Education - Pande Putu Wida Permata Prabawanthi; Made Hery Santosa; Luh Indrayani (Lembaga Pengembangan Kinerja Dosen, 2025)
The study explored the potential of ChatGPT as a learning tool in English language education, focusing on both students’ and lecturers’ readiness and satisfaction. While both groups demonstrated a positive outlook toward the integration of ChatGPT into their learning processes, the research highlighted various nuances in how each group interacted with the technology. Students showed a high degree of readiness in using ChatGPT for basic tasks such as accessing information and enhancing their motivation for learning. However, their readiness for self-directed learning and goal-setting was notably lower, indicating a need for further development in utilizing ChatGPT for more autonomous and personalized learning experiences. This suggests that while ChatGPT can be a useful tool for structured learning, its role in fostering independent learning skills needs to be strengthened. On the other hand, lecturers expressed strong confidence in using ChatGPT for academic purposes, especially in terms of facilitating administrative tasks, grading, and providing additional learning resources. However, they voiced concerns about the potential overreliance on technology, which could hinder the development of critical thinking skills in students. The lecturers stressed the importance of integrating ChatGPT as a supplementary tool, rather than replacing traditional teaching methods that foster deep learning and personal engagement. Thematic analysis of the responses also pointed out that while ChatGPT was appreciated for improving focus and accessibility, it raised concerns about the loss of human interaction in the learning process. Students and lecturers both acknowledged the value of human mentorship, emotional support, and personalized guidance, which ChatGPT could not fully replicate. Therefore, while ChatGPT holds promise for enhancing learning, its integration should be approached with a balanced consideration of technological advantages and the irreplaceable role of human involvement in education.